2018
DOI: 10.1016/j.jacc.2018.04.086
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine in High-Risk Patients With Implanted Cardioverter-Defibrillators

Abstract: In high-risk ICD patients, treatment with ranolazine did not significantly reduce the incidence of the first VT or VF, or death. However, the study was underpowered to detect a difference in the primary endpoint. In prespecified secondary endpoint analyses, ranolazine administration was associated with a significant reduction in recurrent VT or VF requiring ICD therapy without evidence for increased mortality. (Ranolazine Implantable Cardioverter-Defibrillator Trial [RAID]; NCT01215253).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…But, in prespecified secondary endpoint analyses similar to our study, ranolazine administration has been associated witha significant reduction in recurrent VT or VF requiring ICD therapy, without evidence for increased mortality [7]. Another study, conducted by Yeung E et al, showed a significant reduction in median premature ventricular complexes burden, as well as the elimination of VT in chosen patients and the prevention of recurrent defibrillator therapy, something which was also found in our study [8].…”
Section: Discussionsupporting
confidence: 86%
“…But, in prespecified secondary endpoint analyses similar to our study, ranolazine administration has been associated witha significant reduction in recurrent VT or VF requiring ICD therapy, without evidence for increased mortality [7]. Another study, conducted by Yeung E et al, showed a significant reduction in median premature ventricular complexes burden, as well as the elimination of VT in chosen patients and the prevention of recurrent defibrillator therapy, something which was also found in our study [8].…”
Section: Discussionsupporting
confidence: 86%
“…Ranolazine has been used successfully in rodents and large animals to block these changes and prevent the development of hypertrophy, HF, and arrhythmias (Rastogi et al, 2008;Figueredo et al, 2011;Glynn et al, 2015;Liang et al, 2016;Ellermann et al, 2018;Nie et al, 2019). However, results from clinical trials have been mixed with data supporting that ranolazine is safe with questionable efficacy in preventing AF recurrence (RAFAELLO trial), ventricular tachycardia (VT) or ventricular fibrillation (VF) following implantation of cardioverter defibrillator (RAID trial), or improving functional capacity in hypertrophic cardiomyopathy (RESTYLE-HCM trial) (De Ferrari et al, 2015;Bengel et al, 2017;Olivotto et al, 2018;Zareba et al, 2018).…”
Section: Therapeutic Targeting Of the Camkii Signaling Pathwaymentioning
confidence: 99%
“…The RAID clinical trial (NCT01534962) (Zareba et al, 2018) investigated high-risk cardiomyopathy patients who received an implantable cardioverter-defibrillator (ICD). The subjects received either ranolazine (1,000 mg BID) or placebo.…”
Section: Clinical Studiesmentioning
confidence: 99%